Research on the dynamic mechanical properties and constitutive model of metal rubber under impact loading - Youchun Zou; Chao Xiong; Junhui Yin; Kaibo Cui; Xiujie Zhu; Huiyong Deng; Shijun Song (Materials Research Express, 2021)
The development of lightweight, impact-resistant and high energy dissipation materials is of great significance to reduce the hazards of explosions and impacts. Metal rubber (MR) has the characteristics of low density, high damping performance and high elasticity, which shows great potential in the field of protection. However, there are few studies on the dynamic mechanical response of MR under high-speed impact. A series of experiments were carried out to study the mechanical properties of MR. It is found that the deformation mechanism of the metal wire inside the MR determines the mechanical properties. Under quasi-static conditions, the stress-strain of MR includes an elastic stage, a softening stage and a hardening stage, and the stress-strain under high-speed impact includes an elastic stage, a softening stage and a failure stage. In addition, the smaller the wire diameter, the higher the load-bearing capacity of the MR. The damage characteristics of MR under high-speed impact are divided into expansion failure and compaction failure, which will affect mechanical performance in the failure stage. The calculated energy absorption and ideal energy absorption efficiency show that MR is a material with excellent energy absorption properties. The dynamic elastic modulus and dynamic peak stress of MR have strain rate effect and density effect. A constitutive model based on Sherwood-frost equation was established, which can precisely forecast the dynamic mechanical properties.